2018
DOI: 10.3390/md16060190
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Production Conditions, Purification, Identification, and Antioxidant Activity of Violaxanthin from Microalga Eustigmatos cf. polyphem (Eustigmatophyceae)

Abstract: Violaxanthin is a major xanthophyll pigment in the microalga Eustigmatos cf. polyphem, but the amount produced after propagation can vary depending upon culture conditions. In this study, the effects of cultivation time, nitrogen concentration, light intensity, and culture mode on violaxanthin production were investigated. The results showed that this microalga vigorously grew and maintained a high level of violaxanthin in the fed-batch culture, and the highest violaxanthin productivity of 1.10 ± 0.03 mg L−1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…The C16:1 fatty acid was dominant in four of the six investigated species [13]. With its properties, palmitoleic acid is used in biodiesel production and as an ingredient of cosmetics, functional foods, and pharmaceuticals [13]. As shown in this study, extension of the lighting time from 16 to 24 h promoted the accumulation of the C16:1 acid in Eustigmatos magnus cells.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The C16:1 fatty acid was dominant in four of the six investigated species [13]. With its properties, palmitoleic acid is used in biodiesel production and as an ingredient of cosmetics, functional foods, and pharmaceuticals [13]. As shown in this study, extension of the lighting time from 16 to 24 h promoted the accumulation of the C16:1 acid in Eustigmatos magnus cells.…”
Section: Discussionsupporting
confidence: 54%
“…Eustigmatophyceae are characterized by the presence of chlorophyll a only, but no content of chlorophylls b and c. Violaxanthin, vaucheriaxanthin, zeaxanthin, and β-carotene are their main pigments [12,13]. The decrease in the chlorophyll a content in the Eustigmatos magnus cells observed in this study in the continuous lighting variant was caused by the appearance of its oxidized forms in the CL HL experiment.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…In agreement with this data, and underlining the effect of the nitrogen concentration on SM production, Wang et al showed that either very high or insufficient nitrogen concentrations limited the ability of the microalga Eustigmatos cf. polyphem to produce the antioxidant pigment violaxanthin [ 45 ].…”
Section: Change In Nutrient Regimesmentioning
confidence: 99%
“…Up to now this red-coloured pigment is sometimes used as a food colourant under the general E number E161e but it is not yet approved for use as a food additive in the EU or the USA [24,27]. ViX has demonstrated strong radical scavenging activity, valid inhibition of lipid peroxidation and red blood cell hemolysis, anti-proliferative, anti-inflammatory and proapoptotic activity against human cancer cell lines in vitro, which indicated that this pigment has great potential to be widely applied in healthcare and medical products [28,29].…”
Section: Carotenoids Of Eustigmatophyceaementioning
confidence: 99%